Ubiquitous computer at school. Case study on tablet deployment project in elementary school «EduTablettes-86» – French - Espinoza Bueno, José María (2015)
This research is part of an exploratory study that focuses on the observation and analysis of the integration of the tablet in the classroom, and it takes part of the «EduTablettes-86» project (Poitiers, France). This study addresses the «pervasive computing» or «ubiquitous computing» as an approach that allows us to understand the direction of technology and its relation to the use of the tablet in the school, in addition, the theory of «situated action» is used as a reference and it makes possible to study the tablet in an application context, besides that, it includes the notion of communication «Human-Machine» to understand and to reflect on the interaction: teacher-student-tablet. We made use of the «ethnomethodology» as a method to understand the organization and structuring of a class session.